(untitled) (Journal of Science and Technology, 2016)
Recent Ghanaian history has been characterized by change and it is thus not surprising that the theme of change should feature so prominently in the works of Ghanaian novelists. R.E. Obeng, Ayi Kwei Armah and Kofi Awonoor are among Ghanaian novelist who accord this theme treatment in their novels and they are able to do this through a careful manipulation of the different linguistic resources at their disposal.